Serendipity in Relationship: A Tentative Theory of the Cognitive Process of Yuanfen and Its Psychological Constructs in Chinese Cultural Societies - Hsu, Hsin-Ping; Hwang, Kwang-Kuo (Frontiers in Psychology, 2016)
The main purpose of this article is to combine three important themes in Chinese cultural societies: serendipity in relationship (yuanfen), relational interactions, and psychological adaptation through self-cultivation. People who live in Chinese cultural societies are deeply affected by relationalism and tend to be very different from their Western counterparts, who adopt individualistic methods when dealing with interpersonal problems. They are highly likely to access the perspective of yuanfen as part of their cultural wisdom to convert negative feelings, awkwardness, or setbacks caused by interpersonal relationship incidents, into a type of cognitive belief that can be used to combat anxiety and actuate coping actions. Based on this, this article proposes the tentative theory of a dialectical model which comprises elements of the philosophies of Daoism, Buddhism and Confucianism, to analyze the cognitive operation process regarding yuanfen and to explain and predict how people in Chinese cultural societies differ from most Western people in terms of psychological adjustment and coping actions when dealing with interpersonal problems. Canonical correlation analysis was used in the empirical study to describe this model and resulted in two statistically significant canonical factor pairs. The hypothesized model has been partially verified. It is hoped that this framework can serve as a pilot perspective for future studies, and at the same time provide the Western academic world with a reference for understanding the concept and substantive effects of serendipity in relationship. Further suggestions for future research direction are offered.